Impact of Covid -19 Pandemic on Education System - Akram, Muhammad; Rehman, Urooj; Ahmed, Misbah (Asian Journal of Science, Technology, Engineering, and Art, 2025)
The symptoms of COVID-19 pandemic are similar to those of Severe Acute Respiratory Syndromewhich is a group of viral diseases linked to respiratory infections. The first SARS case was reported in remote and ancient areas of China in 2003, and it quickly spread throughout the world. In order to combat the global epidemic, the World Health Organization has worked with numerous health experts worldwide. In a time record, students are separated from their physical spaces, providing essential social connections, to spend extended hours seated behind a screen. Most countries have seen a slower rate of adoption of online learning platforms, which have been driven mostly by educational institutions that already had operational digital learning platforms.